Quotas : Updated Calculations and Data Adjustments. (Policy Papers; Policy Paper ;, 2007)
This paper presents the results of updating the data set for quota calculations through 2005. The updated data set would provide the basis for the next round of discussions on quota and voice reforms. The paper also revisits the issue of data adjustments. Consideration of a broader range of specifications for a new quota formula is left for the next paper on quota and voice reforms being issued concurrently.